(untitled) (Research, Society and Development, 2024)
The objective of this study is to evaluate the influence of diet and its correlation with the psychomotor development of infants with congenital syphilis at Santa Isabel Hospital and Maternity in Aracaju, SE. This topic is of public health interest due to the increasing number of cases of the disease in northeastern Brazil and the lack of available information on the subject. For the study, data were collected from children aged 0 to 2 years diagnosed with congenital syphilis, accompanied by their guardians. The research process involved interviews with parents regarding the child’s habits and the application of the Denver II Test. A correlation was then established between diet and patient development, highlighting the importance of further studies on this subject, considering the numerous factors that can influence growth and the acquisition of new skills in children. Additionally, the study emphasized the need for direct intervention in risk factors to prevent the sequelae of the disease in this population.